Newborns' MicroRNA Expression as Potential Biomarkers for Disease Diagnosis - Isea, Raúl (International Journal of Neonatology, 2024)
The work emphasizes the need for additional research to create novel biomarkers based on the use of microRNAs as a less invasive and precise diagnostic technique for identifying diseases in newborns.
Keywords: Newborn; microRNA; biomarker; Diagnosis